P Pengaruh Penerapan Game Based Learning Terintegrasi Desmos Terhadap Peningkatan Kemampuan Numerasi Siswa Pada Materi Eksponen - Seftiawati Nuriyatun Nikmah; Nani Ratnaningsih; Elis Nurhayati (MUST: Journal of Mathematics Education, Science and Technology, 2025)
Numeracy is an essential skill in understanding and applying mathematical concepts in everyday life, but in exponent material this skill still needs to be improved. This study aims to examine the improvement and influence of the application of Desmos integrated Game Based Learning on students' numeracy skills, using a quantitative approach with a pre-experimental method of one group pretest-posttest design on class X.E-12 students of SMA Negeri 3 Tasikmalaya. Data were analyzed through descriptive statistics, Shapiro-Wilk test, Paired Sample t-Test, N-Gain, and Cohen's d. The results showed an increase in students' numeracy skills, evidenced by the calculated t value (46.400) ≥ t table (2.032), so that the posttest score was better than the pretest. The average N-Gain was 0.6995 (moderate), with 57.14% of students in the moderate category and 42.86% in the high category. The increase per indicator includes the use of numbers and basic mathematical symbols in everyday life of 0.8263 (high), analysis of information from various forms of data presentation of 0.7035 (high), and interpretation of analysis results to predict & make decisions of  0.6269 (moderate) with a very large influence category based on the Cohen's d value obtained.